2022
DOI: 10.1002/fsn3.3145
|View full text |Cite
|
Sign up to set email alerts
|

Is vitamin D deficiency influenced by obesity during the first 5 years of life? A cross‐sectional multicenter study

Abstract: Evidence on the association of 25‐hydroxyvitamin D (25[OH]D) and obesity during the first 5 years of life is limited in China. The objective of this study was to examine the associations between weight, weight for age z score (ZWAZ), weight for length/height z score (ZWHZ), and body mass index for age z score (ZBMI) and 25(OH)D. This was a large population‐based cross‐sectional multicenter study in which the children aged 0–5 years were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In our previous study, vitamin D de ciency was observed in children with greater adiposity during the rst 5 years of life (5). However, the mehcanism has not been well-de ned.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our previous study, vitamin D de ciency was observed in children with greater adiposity during the rst 5 years of life (5). However, the mehcanism has not been well-de ned.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous study was a large population-based cross-sectional multicenter study in which 5289 children aged 0-5 years were recruited from 12 Children's Health Care Centers by a strati ed cluster random-sampling method in 10 cities of Jiangsu Province, China. The results showed that the prevalence of VD de ciency in 0-5 years children was 30.1% (4), and the prevalence of VD de ciency in 0-5 years children with obesity and non-obesity was 36.0%, 29.8%, respectively, there were all signi cant difference (5). Vitamin D de ciency was observed in children with greater adiposity during the rst 5 years of life.…”
Section: Introductionmentioning
confidence: 89%